Diversity and Abundance of Earthworms in Different Landuse Patterns: Relation with Soil Properties - Singh, Sharanpreet; Singh, Jaswinder; Vig, Adarsh Pal (Asian Journal of Biological and Life Sciences, 2020)
The earthworms are the most important soil species because of their important role in the distribution of soil nutrients. The objective of the study was to know the earthworm diversity and their abundance in different land use pattern of Punjab (India) and how their diversity related to soil physico-chemical properties. The earthworm collections were perfomed in different land use system viz. Garden, Agricultural Field, Forest, Grassland and Leaf litter sites. The physico-chemical properties and heavy metal analysis of the soil were also done by using standard protocols. The statistical anaylsis of the data was also performed by using statistical softwares. Total five species of earthworms viz.Metaphire posthuma, Lampito mauritii, Amynthas morrisi, Metaphire houlletiandOctochaetona beatrix. The abundance of earthworms was significantly (p < 0.05) different with order of their abundance was Garden > Grassland > Forest > Leaf litter > Agricultural field. The M. posthuma was reported from all the collection sites whileL. mauritiiwas reported at only three collection sites. The distribution ofA. morrisi, M. houlletiandO. beatrixwere reported from only single collection sites. The physico-chemical properties of the soil samples collected from all the sampling sites were varied significantly (p< 0.05). Factor analysis also proved the direct relation of earthworm abundance on soil physico-chemical properties. We recommend that the farmers should be awared regarding the importance of earthworms diversity in their fields and should also be encouraged to shift their agricultural practices from conventional to non-conventional to improve the diversity of earthworms in the agricultural fields.
Keywords: Abundance; Diversity indices; Earthworm; Factor analysis; Physico-chemical properties